1998
DOI: 10.1007/bf02550564
|View full text |Cite
|
Sign up to set email alerts
|

Subureteric polydimethylsiloxane injection in the treatment of vesico-ureteric reflux

Abstract: Endoscopic treatment of vesico-ureteric reflux is a viable alternative to open surgery. We evaluated the effectiveness of polydimethylsiloxane in the endoscopic treatment of vesico-ureteric reflux. In the period between September 1994 and March 1996, 30 ureteral units of 20 children with vesico-ureteric reflux were treated by means of subureteric polydimethylsiloxane injection. Median age was 8 years in the group including 8 female and 12 male patients. Of the 30 ureteral units, 26 had no reflux at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…[2930] Nowadays, Deflux and Macroplastique are the most frequently used bulking agents with a reported success rate between 68% and 90%. [3132]…”
Section: Discussionmentioning
confidence: 99%
“…[2930] Nowadays, Deflux and Macroplastique are the most frequently used bulking agents with a reported success rate between 68% and 90%. [3132]…”
Section: Discussionmentioning
confidence: 99%
“…The use of injectable materials, e.g. polydimethylsiloxane (PDS) in the treatment of VUR in children has been reported [1,2]; reflux is also a common urological abnormality among patients with chronic renal failure (CRF) [3]. Because reflux is associated with recurrent UTI, it must be treated promptly before kidney transplantation.…”
Section: Indicationsmentioning
confidence: 99%
“…Deflux represents a new biocompatible material without immunogenic properties and a lack of distant migration. Previous studies indicated high success rates of 68% to 90% with endoscopic injection using Macroplastique or Deflux [5-7]. …”
Section: Introductionmentioning
confidence: 99%